Genetic Evidence Supporting a Causal Role of Snoring in Erectile Dysfunction - Xiong, Yang; Zhong, Xin; Zhang, Fuxun; Wang, Wei; Zhang, Yangchang; Wu, Changjing; Qin, Feng; Yuan, Jiuhong (Frontiers in Endocrinology, 2022)
Background The association between snoring and erectile dysfunction (ED) is inconsistent in multiple observational studies. To clarify the causal association of snoring on ED, we performed this two-sample Mendelian randomization study. Materials and Methods The single nucleotide polymorphisms (SNPs) associated with snoring were retrieved from the UK biobank cohort with 314,449 participants (117,812 cases and 196,637 controls). The summary statistics of ED were obtained from the European ancestry with 223,805 subjects (6,175 cases and 217,630 controls). Single-variable Mendelian randomization (MR) and multivariable MR were used to assess the causal relationship between snoring and ED. Results Snoring increases the risk of ED (Odds ratio [OR] = 3.45, 95% confidence interval [CI] = 1.68 - 7.09, P < 0.001) in the inverse variance weighting estimator. In sensitivity analyses, the ORs for the weighted median, MR robust adjusted profile score, and MR Pleiotropy Residual Sum and Outlier approach, MR-Egger, and maximum likelihood method are 5.70 (95% CI = 1.19 - 27.21, P < 0.05), 3.14 (95% CI = 1.01 - 9.72, P < 0.05), 3.11 (95% CI = 1.63 - 5.91, P < 0.01), 1.23 (95% CI = 0.01 – 679.73, P > 0.05), and 3.59 (95% CI = 1.07 – 12.00, P < 0.05), respectively. No heterogeneity and pleiotropy are observed (P for MR-Egger intercept = 0.748; P for global test = 0.997; P for Cochran’s Q statistics > 0.05). After adjusting for total cholesterol, triglyceride, low-density lipoprotein, and cigarette consumption, the ORs for ED are 5.75 (95% CI = 1.80 - 18.34, P < 0.01), 4.16 (95% CI = 1.10 - 15.81, P < 0.05), 5.50 (95% CI = 1.62 - 18.69, P < 0.01), and 2.74 (95% CI = 1.06 - 7.10, P < 0.05), respectively. Conclusion This study provides genetic evidence supporting the causal role of snoring in ED.